Performance Analysis of Unmanned Aerial Vehicle Enabled Wireless Power Transfer Considering Radio Frequency System Imperfections. (15th March 2023) - Lahiry, Archiman; Le, Khoa N.; Bao, Vo Nguyen Quoc; Tam, Vivian W.Y.
Abstract: A simple and energy-efficient communication system configuration is proposed for Unmanned Aerial Vehicle Energy Transmitters (UAV-ETs) for Wireless Power Transfer (WPT) applications. The results show that the proposed UAV-ET's hardware configuration improves WPT time by 9 . 305 %, and reduces UAV-ET's power consumption by 7 . 47 % compared to the UAV Base Stations (UAV-BSs). Also, in the prior works on UAV-enabled WPT the UAV-ET's communication system configuration was not proposed, and UAV-ET's radio frequency component's real-world imperfections were ignored. Therefore, the work proposes a holistic energy efficiency optimization framework for UAV-ETs and hardware design parameters for qualifying the UAV-ET's hardware components to maximize UAV-ET's WPT time. Additionally, a three-dimensional UAV-ET placement optimization is proposed for maximizing WPT time, and results show that higher UAV-ET heights above the Wireless Energy-Receivers (WERs) decrease the WPT time by 4 . 75 % . Besides, the results suggest that Antenna Array (AA) losses and the power amplifier's power added efficiency variation reduce UAV-ET's WPT time by 16 . 48 % . Finally, a 115 g crossed-slotted waveguide AA for UAV-ET is manufactured using laser cutting, and the experiments confirm that the AA's total loss is 0.72 dB, therefore, the AA qualifies requirements according to the proposed UAV-ET's hardware component design optimization framework. Highlights: An aerial energy transmitter communication system configuration is proposed. Framework to minimize power consumption of aerial energy transmitters proposed. The framework considers realistic hardware imperfections. A low-loss aerial energy transmitter antenna array is manufactured.